A pilot trial of all-terrain vehicle safety messaging in a movie theatre. (1st March 2011) - Graham, J; Mullins, S Hope; Miller, B; Nixon, J; Eoff, S; Brann, M; Aitken, M E
Abstract : Introduction: All terrain vehicle (ATV) injuries are increasing among rural children and adolescents. Methods to effectively promote ATV safety messages are not well described. The purpose of this study was to determine the feasibility of using a movie theatre as a venue for ATV injury prevention. Methods: A public service announcement on ATV safety was shown in a rural movie theatre in Arkansas, USA, for a period of 8 weeks in the summer, 2009. Patrons were asked to complete exit surveys by trained volunteers. The survey tested the recall of messages in the movie previews, including the ATV announcement. χ 2 was used to determine statistical significance. Results: 703 movie patrons completed the survey; 508 reported arriving in the theatre before the previews started and 195 reported arriving after the previews. Of those arriving before the previews, 75% recalled an ATV safety message versus. 23% of those who arrived after the previews (p<0.0001). More patrons remembered the ATV announcement than an advertisement for a popular soft drink (75% vs 58%, p<0.0001). More patrons arriving before the previews reported agreeing with the safety message than those arriving after previews (90% vs 75%, p<0.0001). Conclusions: This trial demonstrated that an ATV safety message shown in a rural movie theatre is associated with rates of recall higher than commercial advertising shown in the same preview and is associated with high rates of agreement with the primary safety message. This strategy may be effective in spreading injury prevention messages.